Depth profile analysis of rare earth elements in corroded steels by pulsed glow discharge – time of flight mass spectrometry. Issue 7 (13th June 2017) - Muñiz, Rocío; Lobo, Lara; Kerry, Timothy; Sharrad, Clint A.; Pereiro, Rosario
Abstract : Depth profiling with PP-TOFMS of REEs (as substitutes of radioactive elements) in studies of stainless steel corrosion and contaminant uptake. Abstract : Depth profiling of 304L stainless steel surfaces exposed to rare earth nitrate solutions over varying time lengths has been undertaken using the recently commercialized "PP-TOFMS Plasma Profiling Spectrometer" by Horiba. This combines a pulsed glow discharge source with a time-of-flight mass spectrometer (TOFMS) which allows elemental depth profiling with nanometric resolution of almost all elements of the periodic table. In this work special attention is paid first to the optimization of the new PP-TOFMS for depth profile analysis of low concentrations of rare earth elements (REE) in the samples. Sensitivity given in [(cps X × sputtering rate in μg s −1 )/(μgX g −1 )], being the concentration of the element X (μgX g −1 ) corrected by the abundance of the measured isotope, was in the order of 20 for all REEs under investigation. Moreover, a quantification strategy for these samples resembling the relative sensitive factors concept has been developed. Validation was done using a homogeneous reference material containing certified concentration values for La (6 ± 1 μg g −1 ), Ce (14 ± 1 μg g −1 ) and Nd (6 ± 1 μg g −1 ). Concentrations of 4 ± 1 μg g −1, 13 ± 1 μg g −1 and 5 ± 1 μg g −1 were calculated for La, Ce and Nd respectively with the proposed strategy. Quantitative depth profiles of the investigated samples have shown that the contaminants did not penetrate the substrate deeper than 80 nm even after a month of exposure to 12 M HNO3 .